Pengembangan Media Pembelajaran Power Point Interaktif Materi Persamaan Kuadrat Kelas X SMK Negeri 9 Pangkep - Sunardi J; Haerul; Rukli; Muhammad Safrullah Saleh (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The lack of variety in mathematics learning media causes students' interest in learning to decrease. For this reason, it is necessary to develop various learning media, one of which is technology-based media. The purpose of this research is to produce an interactive PowerPoint. This type of research is Research and Development using the 4D research model. Data collection techniques through a questionnaire. The instruments used were validation sheets and student questionnaire responses sheets. The subjects of the study were 20 students of SMK Negeri 9 Pangkep with 20 students. The data obtained is qualitative data and then converted to quantitative data using the Method of Summated rating technique. The results showed that the developed media was declared valid with a percentage of two expert validators at 87% and from the questionnaire responses of students at 76% with practical categories.